The Roman object revolution objectscapes and intra-cultural connectivity in northwest Europe - Pitts, Martin (Amsterdam archaeological studies ;, 2019)
This book explores a major step-change in Eurasian history: the revolutionary boom in standardised objects at the start of the Roman era. The far-reaching impacts of this revolution are addressed through an examination of the circulation and selections of thousands of standardized pots and brooches, with particular emphasis on funerary repertoires, c. 100 BC - AD 100. Breaking with the national frameworks that inform artefact research in much 'provincial' Roman archaeology, the book tests the idea that marked increases in the movement of people and objects fostered pan-regional culture(s) and transformed societies. Using a rich database spanning a swathe of northwest Europe, the study is one of the first to extensively apply multivariate statistics (such as correspondence analysis) to material of this kind, enabling a move from disconnected regional studies, sites and assemblages to new understandings of a more richly complex cultural milieu.